2016
DOI: 10.4067/s0718-34292016005000038
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de diferentes mulches orgánicos sobre el cultivo de brócoli (Brassica olerácea L. var. Itálica) en Ecuador

Abstract: Efecto de diferentes mulches orgánicos sobre el cultivo de brócoli (Brassica oleracea L. var. Italica) en Ecuador Effect of different organic mulches on growing broccoli (Brassica oleracea L. var.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…italica Plenck) crop, the use of black oat straw reduced weed density by up to 43% (Frutos et al, 2016). Besides functioning as a barrier to the passage of light and the emergence of the soil seed bank, black oat straw has a strong allelopathic inhibitor effect on some weed species (Rueda-Ayala et al, 2015), inhibiting, for example, the germination and growth of Euphorbia heterophylla L. (Hagemann et al, 2010), one of the main species identified in the present study.…”
Section: Resultsmentioning
confidence: 50%
“…italica Plenck) crop, the use of black oat straw reduced weed density by up to 43% (Frutos et al, 2016). Besides functioning as a barrier to the passage of light and the emergence of the soil seed bank, black oat straw has a strong allelopathic inhibitor effect on some weed species (Rueda-Ayala et al, 2015), inhibiting, for example, the germination and growth of Euphorbia heterophylla L. (Hagemann et al, 2010), one of the main species identified in the present study.…”
Section: Resultsmentioning
confidence: 50%